Tackling Private Over-Indebtedness in Asia : Economic and Legal Aspects - Garrido, Jose (IMF Working Papers; Working Paper, 2020)
One consequence of interest rates remaining 'too low for too long' since the Global Financial Crisis is the buildup in private leverage in emerging economies. These vulnerabilities have been laid bare by the COVID-19 shock. This paper employs the growth at risk framework (Adrian, Boyarchenko, and Giannone, 2019) to examine how different types of private leverage present risks to future GDP growth in Asian economies. We find evidence that private leverage can boost GDP growth in the near term, but can increase the risks of low growth over the medium term. For our sample, we also find that household debt poses a larger drag on future GDP growth than corporate debt. In the second part of the paper, we provide an overview of a strategy for prevention and resolution of over-indebtedness, with a focus on legal tools, and with considerations to account for the consequences of the COVID-19 pandemic. Using a novel cross-country survey, we examine the role of legal techniques to prevent and treat corporate and household over-indebtedness, benchmarking those in ASEAN-5, China, India, Japan and Korea against international best practice. The analysis can inform a country-specific prioritized approach to strengthening legal frameworks.